Dieulafoy lesion in the jejunum: a rare cause of massive gastrointestinal bleeding - Olubunmi Oladunjoye; Adeolu Oladunjoye; Lydia Slater; Asad Jehangir (Journal of Community Hospital Internal Medicine Perspectives, 2020)
Dieulafoy lesions are tortuous vascular malformations characterized by thick walled submucosal arteries/large caliber arterioles protruding through a small mucosal defect surrounded by normal mucosa. They can occur in the jejunum/ileum and can cause massive, life-threatening GI bleeding. We present an 80-year-old female with three weeks of black tarry stools, progressive dyspnea on exertion and generalized body weakness with no significant findings on Esophagogastroduodenoscopy (EGD). Push enteroscopy revealed a Dieulafoy lesion in the proximal jejunum and an overlying clot, with oozing of blood noted after clot removal. The lesion was treated with Argon plasma coagulation (APC) and a post-APC fleshy protuberance was clipped to secure hemostasis. It is therefore important to keep a high index of suspicion for jejunal/ileal Dieulafoy lesions in patients with massive GI bleeding of unclear etiology on EGD/colonoscopy.